The baric coefficient of resistance of Mn1.9Cr0.1Sb as measured by the double AC method - Morchshakov, V.; Medvedeva, I. V.; Boshta, M.; Saber, M.; Baerner, K.; Gueven, H.; Annaorazov, M. P. (Elsevier Science Sa, 2008)
The baric coefficient of resistance of the magnetocaloric cycle working medium Mn1.9Cr0.1Sb, aside from the peak which is expected and related to the pressure shift of the AF-Fr transition temperature T-s(p), shows two sidebands which are probably related to the percolation of phase domains. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: magnetically ordered material; first-order phase transition; baric coefficient of resistance; double AC method